2019
DOI: 10.1002/advs.201801826
|View full text |Cite
|
Sign up to set email alerts
|

Driving Cells with Light‐Controlled Topographies

Abstract: Cell–substrate interactions can modulate cellular behaviors in a variety of biological contexts, including development and disease. Light‐responsive materials have been recently proposed to engineer active substrates with programmable topographies directing cell adhesion, migration, and differentiation. However, current approaches are affected by either fabrication complexity, limitations in the extent of mechanical stimuli, lack of full spatio‐temporal control, or ease of use. Here, a platform exploiting ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…For instance, studies have recently demonstrated that a biocompatible azopolymer can efficiently control the phenotype of neurons by influencing how cells respond to the nanometric grooves: i.e., by promoting a synaptic formation of multiple neurites or the elongation of single predominant neurites along preferential directions over time [40]. In the current scenario, complex topographies could be instructed on demand, under a controlled light stimulation, with arbitrary spatial distributions over a wide range of spatial and temporal scales [41]. In this perspective view, the route toward the design of bioinspired materials that are able to dynamically interact and/or instruct cells for innovative approaches in tumor diagnosis and in vivo cancer modeling can be traced.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have recently demonstrated that a biocompatible azopolymer can efficiently control the phenotype of neurons by influencing how cells respond to the nanometric grooves: i.e., by promoting a synaptic formation of multiple neurites or the elongation of single predominant neurites along preferential directions over time [40]. In the current scenario, complex topographies could be instructed on demand, under a controlled light stimulation, with arbitrary spatial distributions over a wide range of spatial and temporal scales [41]. In this perspective view, the route toward the design of bioinspired materials that are able to dynamically interact and/or instruct cells for innovative approaches in tumor diagnosis and in vivo cancer modeling can be traced.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in order to transfer a pattern from the mold to polymeric films deposited on flexible [ 107 ], solid [ 108 ], or textile [ 3 ] substrates, molds are mechanically pressed against a polymer melt [ 109 ] or films while heating the latter to melting temperatures [ 110 , 111 ] ( Figure 5 a). For efficiency reasons, it is also possible to press the molds against films soaked with non-solvents to form surface “gels” [ 112 ], or against as drop-cast solutions [ 113 ] or even to poor solutions of interest directly on the mold [ 114 ] and heat afterwards.…”
Section: Top–down Lithographic Methodologiesmentioning
confidence: 99%
“…There is a variety of structures that can be obtained with TNIL ( Table 2 ) and employed in different biological applications [ 111 , 113 , 114 , 119 , 120 ], organic photovoltaics [ 121 ], interfaces [ 122 ], superhydrophobic surfaces [ 107 ], memory elements [ 123 ], dental implants [ 124 ], etc. Miniaturized patterns obtained by TNIL and consisting in poly(benzyl methacrylate) (PBMA) lines/2D gratings and nanoholes were recently reported [ 87 ] ( Figure 6 a–b).…”
Section: Top–down Lithographic Methodologiesmentioning
confidence: 99%
“…[ 17,25,115–118 ] Other applications of switchable surfaces include biomedical applications, such as regulating the cell adhesion, spreading, shaping, proliferation, migration, and differentiation. [ 15,119–122 ]…”
Section: Application Of Switchable Surfacesmentioning
confidence: 99%